Blended learning with Edmodo: The effectiveness of statistical learning during the COVID-19 pandemic - Rini Sefriani; Rina Sepriana; Indra Wijaya; Popi Radyuli; Menrisal Menrisal (International Journal of Evaluation and Research in Education (IJERE), 2021)
The condition of all countries in the world is devastated by the presence of a corona virus epidemic known as Corona Virus Diseases-19 (COVID-19). The efforts of the Indonesian government to break the chain of distribution of COVID-19 in the midst of society is to impose a policy of keeping distance, avoiding publicity, frequent hand washing and wearing masks. This also has an impact on the field of education where learning from home is also known as work from home (WFH). Learning is done with an online learning system that at least applies distance, physical social protection. Blended learning is one that is done using the Edmodo application, which can be done online at home. The purpose of this study is to find out how effective the use of the blended-learning learning model with Edmodo applications is to students of Informatics Engineering Education during the COVID-19 pandemic. This research is a quasi-experimental design with a pre-test and post-test control group. The results of this study indicate that the use of Edmodo's blended-learning learning model in Information Technology Education students during the COVID-19 pandemic period is effective and can be used as a virtual learning solution.